1975
DOI: 10.4315/0022-2747-38.6.347
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Delicatessen Foods: Are Standards Needed?

Abstract: Surveillance of seven types of delicatessen salads (chicken, egg, ham, macaroni, American potato, shrimp, and tuna) was conducted from March through July, 1974. Liver spread and sandwich spread were included in the sampling. Products were obtained from approximately 150 retail establishments. A separate surveillance of one central production unit and approximately 18 retail establishments, which it supplied, was also conducted. Twenty six percent to 85% of samples of products obtained from general retail outle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similarly, pH did not seem to influence the quality of the products since low pH was not always reflected in low counts of the products. Pace (11) also reported that pH values did not influence the microbial content of delicatessen salads. However, generally samples with low pH values of close to 5.0 did not show significant bacterial multiplication on storage.…”
Section: Moisture and Phmentioning
confidence: 97%
“…Similarly, pH did not seem to influence the quality of the products since low pH was not always reflected in low counts of the products. Pace (11) also reported that pH values did not influence the microbial content of delicatessen salads. However, generally samples with low pH values of close to 5.0 did not show significant bacterial multiplication on storage.…”
Section: Moisture and Phmentioning
confidence: 97%
“…The state of New Jersey and the Armed Forces have established an APC limit of 105/g for salads (4,5,9). When incubated at 35°C, 13.5% of the salads exceeded this limit.…”
Section: Resultsmentioning
confidence: 99%
“…Higher concentration of coliform count in the raw beef meat is assumed to be an indicator of fecal contamination and fresh meats sold to the public in open markets are grossly contaminated with coliform bacteria. According to Pace (1975) and Solberg et al (1986), coliform count higher than 10 2 /g in delicatessen food products are indicative of dangerous contamination.…”
Section: Discussionmentioning
confidence: 99%